2015
DOI: 10.1002/ptr.5384
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Bronchodilator Activity of Salvia officinalis (Sage): Possible Involvement of K+ Channel Activation and Phosphodiesterase Inhibition

Abstract: The aqueous methanolic extract of the aerial parts of Salvia officinalis (So.Cr) was studied to provide possible underlying mechanism(s) for its medicinal use in asthma using the in vivo bronchodilatory assay and isolated tracheal preparations. S. officinalis (1-10 mg/kg) dose-dependently inhibited carbachol (CCh)-induced bronchospasm in anesthetized rats with three-fold greater potency than the positive control, aminophylline. In tracheal preparations, So.Cr inhibited the low K (25 mM)-induced contractions. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Potassium channel opener drugs have widespread therapeutic use in gastrointestinal disorders like diarrhea, 32 in CVS as antihypertensive, 33 and as bronchodilator in hyperactive airways diseases like asthma and cough. 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium channel opener drugs have widespread therapeutic use in gastrointestinal disorders like diarrhea, 32 in CVS as antihypertensive, 33 and as bronchodilator in hyperactive airways diseases like asthma and cough. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Potassium channel opener drugs have widespread therapeutic use in gastrointestinal disorders like diarrhea, 32 in CVS as antihypertensive, 33 and as bronchodilator in hyperactive airways diseases like asthma and cough. 34 Cromakalim (ATP dependent K + channel opener) inhibited low K + induced contractions. To confirm the K + channel activation mechanism, low-K + triggered contractions pretreated with glibenclamide was tested with extract doses which inhibited its relaxing effect having similar pattern as cromakalim confirmed opening of K + -ATP channel.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of its known constituents, chrysoeriol, was found to exhibit high selectivity for its inhibitory effect on airways compared with other smooth muscles (Khan and Gilani, ), thus showing potential to be developed for airways disorders. Interestingly, few recent studies on Morus alba , Salvia officinalis (Sage) and Vitex negun showed that their bronchodilator action is mediated through a combination of predominant K + channel activation, PDE inhibition and reasonable Ca ++ channel blockade (Khan et al , ; Gilani et al , ; Khan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The tissues were initially incubated for 30 min and finally equilibrated for 1 h prior to addition of any chemical agent. K + at low (25 mM) and high (80 mM) concentration was used to stabilize the respective tissue preparations until achievement of constant responses usually after 2 -3 times application followed by washing of the tissue with fresh Kreb's solution [14]. After stabilization state, low and high K + was administered to the tissue to induce sustained contractions, respectively.…”
Section: Animal Studiesmentioning
confidence: 99%
“…To characterize and confirm the type of K + -channels involved in the vasodilating effect, the inhibitory effect of TPPU was reproduced in the aortic preparation pretreated with glibenclamide (Gb, 10 µM), an ATP-dependent K + channel antagonist [16], tetraethyl ammonium (TEA, 10 mM), a nonselective antagonist of the K + channels [17] and 4 -aminopyridine (4-AP, 1 mM), a voltage-dependent K + channel blocker add [14].…”
Section: Animal Studiesmentioning
confidence: 99%